Institutional Satisfaction and Recommendation: What Really Matters to International Students? - Ammigan, Ravichandran (Journal of International Students, 2019)
This quantitative study investigates the role of satisfaction variables as predictors of institutional recommendation for over 45,000 international students at 96 different institutions globally. Using data from the International Student Barometer (ISB), it demonstrates which aspects of the university experience are most significant on students’ propensity to recommend their institution to prospective applicants. This article also discusses key implications and policy recommendations for how university administrators and international educators could enhance the international student experience and strengthen recruitment and retention strategies on their respective campuses.